UNDERSTANDING ISSUES OF AFFORDABLE HOUSING IN MALAYSIA TO ATTRACT INVESTMENT - Mohd Daud, Mohd Ariff; Rosly, Saiful Azhar; Muhamad Sori, Zulkarnain (PLANNING MALAYSIA, 2022)
This study attempts to investigate the issues that impede the provision of affordable housing for Malaysian population. These issues need to be identified and addressed, as they hinder potential private investments in affordable housing projects. In order to achieve this aim, a qualitative method was adopted, in the form of interviews with several developers and institutional investors. Seven areas were recognised to be the sources of major problems with affordable housing in Malaysia namely, the lax policy; poor urban design and planning; supply and demand; property overhang, financing, and price; lacking innovation and research and development; escalating development costs; as well as obsolete quota and subsidy programmes. These findings may provide invaluable insight for policymakers in identifying and resolving the issues of affordable housing, which may then create potential avenue for private investment to alleviate the issue of shortage of affordable housing.